El objeto de la psicología como ciencia: relación sin “cuerpo-substancia” - Ribes-Iñesta, Emilio (Acta Comportamentalia, 2019)
The subject matter of psychology as a science is examined from the viewpoint of the phenomenology of ‘mental’ expressions in ordinary language practices. Different historical attempts to provide body and substance to the subject matter of psychology are revisited: Descartes, Brentano, McDougall, and Watson. The overcoming of this erroneus trend by the field logic proposed by J.R. Kantor, conceiving psychology as relation between an individual and a stimulus object, is examined. Implications of this formulation are discussed in regard to the widening and extensión of the domain of psychoogical phenomena to the animal kingdom, the relationships of psychology with ecobiology and historical social science conceiving psychology as a coextensive science, the concept of ‘individual’ as an outcome of the processes of speciation or socialization, and the density occupied by psychological behavior in the continua of biological and social behaviors.